2018
DOI: 10.1088/1361-6528/aaf150
|View full text |Cite
|
Sign up to set email alerts
|

Sulforaphane-conjugated selenium nanoparticles: towards a synergistic anticancer effect

Abstract: Sulforaphane-modified selenium nanoparticles can be prepared in a simple aqueous-phase redox reaction through reduction of selenite with ascorbic acid. The sulforaphane molecules present in the reaction mixture adsorb on the nanoparticle surface, forming an adlayer. The resulting conjugate was examined with several physicochemical techniques, including microscopy, spectroscopy, x-ray diffraction, dynamic light scattering and zeta potential measurements. As shown in in vivo investigations on rats, the nanomater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The results also demonstrated that Se could potentiate the anti-inflammatory action of Tri on the base of PLNs. The synergistic effect between Se and therapeutic molecules has been widely confirmed [ 34 , 41 , 42 ]. This was well supported by the declined levels of inflammatory factors in the peripheral blood ( Figure 11 F–H).…”
Section: Resultsmentioning
confidence: 99%
“…The results also demonstrated that Se could potentiate the anti-inflammatory action of Tri on the base of PLNs. The synergistic effect between Se and therapeutic molecules has been widely confirmed [ 34 , 41 , 42 ]. This was well supported by the declined levels of inflammatory factors in the peripheral blood ( Figure 11 F–H).…”
Section: Resultsmentioning
confidence: 99%
“…Conjugated nanoparticles prepared by adlayer formation by SFN on selenium exhibited significant anticancer activity and selectivity toward cancer cells as observed in in vitro cytotoxicity experiments. Moreover, the in vivo experiments on male Wistar rats suggested no negative impact, with 48% of the nanoparticles eliminated from the body within 24 h (Krug et al, 2019).…”
Section: Sulforaphanementioning
confidence: 93%
“…Interestingly, most of these studies support the activation of apoptosis in tumour cells by promoting the upregulation of pro-apoptotic BAX and Bak and the downregulation of anti-apoptotic bcl-2 and bcl-xL. Furthermore, sulforaphane-coated selenium and tellurium nanoparticles appear to specifically target tumour cells, whereas normal cells, MCF-10A, have a better tolerance to treatment, as observed in the MTT assay [ 61 , 66 , 67 ]. Sulforaphane nanoparticle therapy in breast cancer has consistently anti-tumour effects and therefore its adjuvant administration in combination with other chemotherapeutic drugs through nanoparticles offers great potential.…”
Section: Anti-tumour Effects Of Sulforaphane Nanoparticles: Promising...mentioning
confidence: 98%
“…Not surprisingly, new perspectives of sulforaphane administration through nano-composite-based therapies have promising results. For instance, the use of nanoparticles of selenium, tellurium, gold-coated Fe 3 O 4 , PEGylated Fe 3 O 4 , monomethoxypol, and based on Fe 2+ and Fe 3+ for the administration of sulforaphane in breast cancer, has recently been documented [ 66 , 67 , 73 , 74 , 75 ]. According to the findings of these studies, the anti-tumour effects of nanoparticle treatment are capable of decreasing the viability of tumour cells such as MDA-MB-231, MCF-7, and SKBR-3.…”
Section: Anti-tumour Effects Of Sulforaphane Nanoparticles: Promising...mentioning
confidence: 99%